2021
DOI: 10.1002/anie.202012801
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous mRNA Triggered DNA‐Au Nanomachine for In Situ Imaging and Targeted Multimodal Synergistic Cancer Therapy

Abstract: The development of versatile nanotheranostic platforms that integrate both diagnostic and therapeutic functions have always been an intractable challenge in precise cancer treatment. Herein, an aptamer‐tethered deoxyribonucleic acids‐gold particle (Apt‐DNA‐Au) nanomachine has been developed for in situ imaging and targeted multimodal synergistic therapy of mammary carcinoma. Upon specifically internalized into MCF‐7 cells, the tumor‐related TK1 mRNA activates the Apt‐DNA‐Au nanomachine by DNA strand displaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 42 publications
0
66
0
Order By: Relevance
“…For cancer therapy, it has been demonstrated that a single treatment modality is usually incapable to eliminate tumors completely and accordingly cannot effectively inhibit proliferation and metastasis of cancer cells [15][16][17][18]. Currently, the research on cancer therapy has gradually shifted from monotherapy to multimodal synergistic therapy, which is the cooperation among two or more treatments with integration into a single nanoplatform for enhanced therapeutic efficiency [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…For cancer therapy, it has been demonstrated that a single treatment modality is usually incapable to eliminate tumors completely and accordingly cannot effectively inhibit proliferation and metastasis of cancer cells [15][16][17][18]. Currently, the research on cancer therapy has gradually shifted from monotherapy to multimodal synergistic therapy, which is the cooperation among two or more treatments with integration into a single nanoplatform for enhanced therapeutic efficiency [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…As aforementioned, multimodal synergistic therapy has drawn considerable attention because it can integrate the functions of different single treatment, which inspires us to attempt the multimodal synergistic therapy by virtue of the versatility of Au(I). [ 28,29 ] It has been well documented that gold atoms can be used as radiosensitizers for radiotherapy, [ 22,50 ] so we then chose a relatively low concentration for the following CCK‐8 tests and adopted X‐ray irradiation to assess the radiosensitization property of TPE‐TTPy‐Au. From the results in Figure A, it was found that the cell viability of the group treated by individual ligand showed no obvious decline, while that group treated by X‐ray or TPE‐TTPy‐Au alone presented a slight decrease.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with monotherapy, multimodal therapy strategies hold all the collective advantages of respective individual treatments with minimized potential side effects, thus yielding a remarkably superadditive therapeutic effect. [ 28–32 ] Thus, the realization of integrating both multimodal imaging and multimodal synergistic therapy in a single AIEgen is extraordinarily appealing. As we mentioned above, gold atoms can be utilized as ideal radiosensitizers for radiotherapy and their enhancement efficiency are unmatched among several high‐Z materials recently developed.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prepare the sticky-flares, 13 nm gold spheres were first prepared by a sodium citrate reduction method. 37 The TEM image in Fig. S1A † demonstrates that the synthesized AuNPs exhibited excellent distribution and good homogeneity with the particle size of 13 nm.…”
Section: Sticky-flare Engineering and Characterizationmentioning
confidence: 97%